Practicing diplomacy simulations, perspectives, and applications - Enverga, Manuel R. III; Tionloc, Javier Rico Israel R. (BlueBooks, 2019)
This book is relevant to students and practitioners who are interested in learning about diplomacy. It moves beyond discussions of historical events and emphasizes real-life application and practice. Diplomacy is not a theoretical field, and as such, students that are interested in it would benefit from both experiences and simulations that would allow them to practice diplomatic skills. Simulations are particularly important and are used as a training tool for aspiring diplomats in Singapore, the United Kingdom, and the United States but seldom used in the Philippines. This resource can also be used in the training of Philippine diplomats, providing them information and skills that are pertinent to their careers.